Prophecy from the periphery: Alain Locke's philosophy of cultural pluralism and adult education - Talmadge C. Guy (Adult Education Research Conference, 1994)
Alain Leroy Locke was born in 1886 during the post-reconstruction era and died a month before the Brown v. Board of Education Supreme Court decision. An intellectual steeped in the realities of color in 20th Century America, Locke possessed a range of interests that makes chronicling and interpreting his career in adult education challenging. Nevertheless, he is most commonly known for his leadership in the New Negro movement of the 1920s. However, he was a leading African American figure in the adult education movement of the 1930s. In 1947 he became president of the American Associate for Adult Education. This paper fills in the gaps in knowledge regarding Alain Locke the adult educator. Particular attention is paid to Locke's philosophy of cultural pluralism and adult education.